2018
DOI: 10.31219/osf.io/ykbce
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

submitted manuscript

Abstract: To evaluate the impact of dietary phosphorus (P) intake on renal function in healthy adult cats, two independent studies were completed. Study 1: 48 cats, 1.7 - 9.1 y, were stratified into control or test diets providing 1.2 or 4.8 g/1000 kcal P (Ca:P 1.2 and 0.6) for 36 weeks. Study 2: 50 cats, 1.4 - 7.8 y, were stratified into control or test diets, providing 1.3 or 3.6 g/1000 kcal P (Ca:P 1.2 and 0.9) for 29 weeks. Health markers, glomerular filtration rate (GFR) and mineral balance were measured at regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
4

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 0 publications
2
15
4
Order By: Relevance
“…It is a progressive disease that can be triggered by a number of genetic and environmental factors (3) . Among acquired causes of the disease, dietary phosphorus (P) has been linked to its development and/or progression, not only in cats (2) , but also in humans (Reviewed in 4) .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is a progressive disease that can be triggered by a number of genetic and environmental factors (3) . Among acquired causes of the disease, dietary phosphorus (P) has been linked to its development and/or progression, not only in cats (2) , but also in humans (Reviewed in 4) .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that inclusion of high levels of soluble P salts in diets, often added for technical, palatability and nutritional reasons, can cause glucosuria and increase blood urea nitrogen content whilst decreasing creatinine clearance (5; 6) . In a recent feeding study (2) , reduced feed intake and vomiting were observed within four weeks in adult cats fed high dietary levels of sodium dihydrogen phosphate (NaH 2 PO 4 ; SDHP) providing 3.6g/1000kcal (4184kJ) P (total P 4.8g/1000kcal; calcium:phosphorus ratio [Ca:P] 0.6). This led to structural and functional changes in the kidneys as indicated by reduced GFR and proteinuria, compatible with early stage CKD.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations